Drought stress-induced physiological and molecular changes in strawberries: an integrated transcriptomic and metabolomic perspective - Qiu, Huimin; Ning, Tiao; Ma, Huilan; Gong, Weijun; Li, Diyan; Niu, Yanfen; Chen, Zebin; Jin, Lu; Han, Chengchou; Tang, Yilian; Deng, Changjun; Zhao, Mingfang; et al. (Frontiers in Plant Science, 2025)
Strawberry (Fragaria × ananassa) is a nutritionally valuable and widely popular fruit worldwide. Drought stress is a key factor affecting strawberry production; however, previous studies lacked in depth research on the physiological, biochemical, and molecular regulatory mechanism differences among various strawberry varieties. This study systematically examined the physiological and molecular responses of two cultivars, ‘Benihoppe’ and ‘Kaorino’, to drought stress. Under mild and severe drought conditions, significant changes were observed in the growth parameters, chlorophyll concentration, antioxidant enzyme activity, and proline accumulation of the two varieties. with ‘Kaorino’ exhibiting superior drought tolerance compared with ‘Benihoppe’. Transcriptomic analysis identified 34,168 differentially expressed genes, including 9,665 upregulated and 24,503 downregulated genes. Venn analysis revealed 229 genes associated with proline biosynthesis, MDA accumulation, and antioxidant enzyme regulation. Transcription factors(TFs) expression was profiled using cross-referenced databases. A total of 8,379 DEGs encoding TFs were identified and classified into 47 TF families, some of which (e.g., NAC and WRKY) are known to be involved in drought stress responses. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses suggest that drought tolerance in strawberry involves the coordinated activation of stress signaling pathways, metabolic reprogramming, hormonal regulation, and defense-related biosynthetic routes, with both shared and cultivar-specific features. Metabolomic analysis revealed dynamic shifts in metabolites associated with osmotic adjustment, antioxidant defense, and hormonal regulation. The integrated multiomics approach enabled the construction of a gene–metabolite regulatory network, clarifying the interactions between gene expression and metabolite accumulation. Key pathways implicated in the drought response included the glycerophospholipid metabolism and MAPK signaling cascade. Lysophosphatidylglycerol acyltransferase(LPGAT) and Sucrose non-fermenting 1-related protein kinase 2(SnRK2) may be key genes affecting the drought resistance differences between two strawberry varieties. These findings provide valuable insights into the physiological and molecular mechanisms underlying drought adaptation in strawberries, offering a theoretical basis for breeding drought-resistant cultivars.